Geothermal energy in Colombia as of 2018 [Energía geotérmica en Colombia hasta 2018] (2020)
Colombia is a country with great potential for the exploitation of geothermal energy due to its high volcanic activity caused by the subduction between the Nazca and South American tectonic plates. However, this energy is yet to be exploited. This article seeks to describe, by means of a literature review and information processing, the current status of geothermal energy in Colombia, including the current regulations, the limitations, the recommendations to develop the geothermal energy, and some of the most important projects, studies, and research papers that have been emerged on the discovery, exploration, and exploitation of geothermal energy within the country, emphasizing the areas where exploration projects have been initiated, such as the Nevado del Ruiz volcano, the Tufiño Chiles Cerro Negro volcanic system, the Azufral volcano geothermal area, and the Paipa geothermal area. Over the years, energy vulnerability in Colombia and a government policy of fostering sustainable development in different territories have generated favorable conditions for the exploitation of geothermal resources. Nevertheless, there are several technical, infrastructural, legal, and institutional barriers that slow the proper development of these projects. © 2020, Pontificia Universidad Javeriana. All rights reserved.